Meningkatkan Ekonomi Keluarga dengan Bank Sampah pada Keluarga Penerima Manfaat (KPM) Program Keluarga Harapan Kecamatan Ngronggot Kabupaten Nganjuk - Muhamad Wildan Fawa'id (LP3M IAIFA Kediri, 2021)
This study explains about improving the family economy with the Waste Bank for beneficiary families (KPM) of the Family Hope Program (PKH) in Ngronggot District, Nganjuk Regency. Rosok has been considered as useless waste, even though this rosok can be sold to rosok collectors and the money can be used for other purposes. KPM was built to collect and sort rosok based on its type and then sell rosok in the posts that have been prepared, which then the money from the sale is included in savings. This is considered easier to empower KPM to get side income outside the main income so that it can help the family economy. This activity is easier than giving KPM livestock and mushroom baglogs because it certainly requires greater funds and the results cannot necessarily be felt.